Quasi-weekly oscillation of regional PM2.5 transport over China driven by the synoptic-scale disturbance of the East Asian winter monsoon circulation - Y. Bai; T. Zhao; K. Meng; Y. Zhou; J. Xiong; X. Sun; L. Shen; Y. Yue; Y. Zhu; W. Hu; J. Yao (Atmospheric Chemistry and Physics)
Regional PM2.5 transport is an important cause of atmospheric environment change. However, the variations in regional PM2.5 transport on a synoptic scale with meteorological drivers have been incomprehensively understood. Therefore, this study is targeted at the quasi-weekly oscillation (QWO) of regional PM2.5 transport over central and eastern China (CEC) with the influence of synoptic-scale disturbance of the East Asian winter monsoon (EAWM) circulation. By constructing the data of daily PM2.5 transport flux in CEC in the winters of 2015–2019, we utilize the extended empirical orthogonal function (EEOF) decomposition and other statistical methods to extract the moving spatial distribution of regional PM2.5 transport over CEC, recognizing the QWO in regional PM2.5 transport with the spatial–temporal variations over CEC. The source–receptor relationship in regional transport of PM2.5 is identified with the 2 d lag effect of the North China Plain, as the upwind source region, on the PM2.5 pollution change in the Twain-Hu Basin, as the downwind receptor region in central China. The QWO of regional PM2.5 transport over CEC is regulated by the synoptic-scale disturbance of the EAWM circulation with the periodic activities of the Siberian high. These findings provide new insights into the understanding of regional PM2.5 transport with the source–receptor relationship and the meteorological mechanism in atmospheric environment change.